PENGARUH MOTIVASI DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA CV. PUTRA ABADI JAYA KABUPATEN TANGERANG - Wiwin Windari; Lia Asmalah (Journal of Research and Publication Innovation, 2024)
This research intends to test, study and analyze the influence of motivation and the physical work environment on employee performance. The method used is quantitative. The population in this study was 65 respondents. The results of the analysis show that motivation has a significant effect on Kalryalwaln's performance with a determination value of 43.4% and obtained t count > t table or (4.422 > 1.998). The physical work environment has a significant influence on work performance with a determination value of 61.3% and obtained t count > t table or (7.557 > 1.998). Motivation in the physical work environment has a significant influence on work performance with the regression equation Y= 1.846 + 0.363X1 + 0.621X2. The determination value was 70.6% while the remaining 29.4% was influenced by other factors. Hypothesis testing obtained f count > f table or (74.292 > 3.15).